2019
DOI: 10.3390/su11072020
|View full text |Cite
|
Sign up to set email alerts
|

Wellness Pursuit and Slow Life Seeking Behaviors: Moderating Role of Festival Attachment

Abstract: Slow lifestyles have become a way for individuals to reduce the amount of stress in their lives. Moreover, along with wellness and slow food, slow life seeking is emerging as an area of study, though little research has been studied at Slow Life Festivals (SLFs) associated with consumers’ wellness pursuits, slow life seeking, and perceptions of slow food. To address this gap, this study examined visitors’ decision-making processes using an extended theory of planned behavior (ETPB) by incorporating wellness pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…“Slow travel” is closely related to sustainable transport, including cycling (Hall et al, 2017). The ETPB has expanded understanding of travelers' sustainable behavior and intentions, adding key variables of wellness pursuit (e.g., overall well‐being), slow life seeking (e.g., keeping slow life), authentic experience (e.g., genuine experience), and slow values (e.g., slowness and happiness) (Chung et al, 2018; Kim et al, 2019). In terms of sustainable consumer behavior, the ETPB has well predicted consumer behavior, including the environmentally significant constructs of climate change awareness and mitigation pursuing actions as well as perception and perceived constraints (Kim & Hall, 2019; Kim & Petrick, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…“Slow travel” is closely related to sustainable transport, including cycling (Hall et al, 2017). The ETPB has expanded understanding of travelers' sustainable behavior and intentions, adding key variables of wellness pursuit (e.g., overall well‐being), slow life seeking (e.g., keeping slow life), authentic experience (e.g., genuine experience), and slow values (e.g., slowness and happiness) (Chung et al, 2018; Kim et al, 2019). In terms of sustainable consumer behavior, the ETPB has well predicted consumer behavior, including the environmentally significant constructs of climate change awareness and mitigation pursuing actions as well as perception and perceived constraints (Kim & Hall, 2019; Kim & Petrick, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mobile apps are today an essential part of everyday life [17]. High-speed Internet access, the increased proliferation of smartphones [2], advances in personalized and interactive apps (e.g., geo-tracking [18]), and the fast rhythm of modern life [19] have created a fertile environment for the adoption of mobile applications. Indeed, the 2.7 billion smartphone users across the world spend 90% of the time they spend on their mobiles on apps [20].…”
Section: Introductionmentioning
confidence: 99%
“…The global resources are gradually exhausted from a hasty consumption lifestyle which causes people to feel stressed and tense (Kim et al , 2019). In response to these threats, tourism researchers have tried to design new modes of tourism (Meng and Choi, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the slow food experience contributes to the tourism and hospitality industry and benefits daily. Despite the increasing number of studies on local food experience (Sims, 2009; Kim et al , 2019), authentic food experience (Li et al , 2021) and ethnic food experience (Ting et al , 2019), very few studies have systematically explored the underlying attributes explicating a slow food experience. In this regard, Björk and Kauppinen-Räisänen (2016) suggested that slow food deserves additional research.…”
Section: Introductionmentioning
confidence: 99%